Доказать тождество:

(y-3)(y+7)-13=(y+8)(y-4)-2

(z-11)(z+10)+10=( z-5)(z+4)-80

a^{2}+b^{2}=(a+b)^{2}-2ab

(a+b)^{2}-2b(a+b)=a^{2}-b^{2}

x^{2}-9x+20=(x-4)(x-5)

(c-4)(c+7)=c^{2}+3c-28

Помогите пожалуйста решить Буду благодарен вам

1

Ответы и объяснения

2011-05-16T21:04:29+04:00
1) (y-3)(y+7)-13=y*y+4y-21-13=y*y+4y-34 (y+8)(y-4)-2=y*y+4y-32-2=y*y+4y-34 2) (z-11)(z+10)+10=z*z-1z-110+10=z*z-1z-100 (z-5)(z+4)-80=z*z-1z-20-80=z*z-1z-100 3) (a+b)(a+b)-2ab=a*a+2ab+b*b-2ab=a*a+b*b a*a+b*b=a*a+b*b 4) (a+b)(a+b)-2b(a+b)=a*a+2ab+b*b-2ab-2b*b=a*a-b*b a*a-b*b=a*a-b*b 5) (x-4)(x-5)=x*x-9x+20 x*x-9x+20=x*x-9x+20 6)(c-4)(c+7)=c*c+3c-28 c*c+3c-28=c*c+3c-28